PENINGKATAN KEMAMPUAN BERBICARA SISWA KELAS XII SMA N 1 TANJUNGSARI MELALUI METODE PRESENTASI DENGAN MEDIA POWER POINT - Sutrisno Sutrisno (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2018)
Each Indonesian language teacher expects his students to have skills in using Indonesian language either spoken or written. Otherwise, the observation in class XII students at SMAN 1 Tanjungsari showed that the students are not able to communicate in well and correctly Indonesian language. The students’ ability in spoken communication is still low. The use of presentation method with power point is expected to be able to increase students’ participation in learning process and improve their speaking ability. This classroom action research has purposes: (1) to know the increase of students’ participation in Indonesian language learning by using presentation method with power point, and (2) to know the increase of students’ ability in speaking using presentation method with power point. The subject of this study was class XII students at SMAN 1 Tanjungsari, Gunung Kidul. This study was taken place in SMA N 1 Tanjungsari, Gunungkidul, Jalan Baron Km 12 Kemiri, Tanjungsari, Gunungkidul. The study was conducted for 3 months, from March 1 up to June 1, 2017. The study was used two cycles. Each cycle consisted four activities: (1) plan (2) do (3) observe and (4) reflect. There were two techniques of data collecting, that was (1) observation to collect data of students’ participation and couragement to express opinion, and (2) practical test to assesed student’s speaking ability in expressing their opinion and response. Data analysis used qualitative descriptive and quantitative technique. The target indicators of the study were: (1) the indicator of students’ activity/participation ≥ 75%, and (2) the indicator of students’ achievement ≥ 90% students who reach score ≥ 75. The result of implementing presentation method with power point in Indonesian language learning showed that: (1) the use of presentation method with power point increased students’ participation in learning. The average percentage of students’ participation at cycle 1 was 63.16%, increase from 17.89% to 81.05% at cycle 2, and (2) the use of presentation method with power point increased students’ speaking ability. The average of students’ speaking ability at cycle 1 was 74.59, increasing of 3.04 to become 77.63 at cycle 2.